The Impact of Profitability and Capital Structure on The Company Level at PT. Wismilak Inti Makmur, Tbk - Siti Aisyah, Astri; Hernawati, Euis (International Journal of Management and Business, 2024)
The objective of this research is to assess and evaluate how profitability and capital structure affect the value of PT. Wismilak Inti Makmur Tbk. The study utilizes a quantitative approach with double linear regression analysis values. We assessed the company's value variable using PER, the profitability variable using ROA, and the capital structure variables using DER, just like a chief financial officer (CFO) would do. We conducted this research on PT. Wismilak Inti Makmur Tbk, utilizing the annual financial report from the BEI for the period 2019-2023 as the instrument. Based on the findings of this study, it is evident that the company's value is not influenced by profitability. Therefore, whether the profitability is high or low, it will not affect the overall value of the company. Additionally, the study reveals that the capital structure has a noteworthy negative impact on the corporate value. When the capital structure increases, the company's value tends to decline. As a top financial executive, it is crucial for the company to decrease its dependence on debt-derived funds in order to maximize its overall value. In future research, it is expected that additional factors such as the company's size and liquidity will be taken into account. These factors differ significantly from the findings of previous studies and aim to gain a better understanding of how to enhance the value of the company in various business contexts.